Fresno's Martin Luther King, Jr. March from City Hall to Saroyan Theatre - Watkins, Howard::::::::: (1987)
Howard Watkins wearing green and brown dashiki; Roosevelt Black Student Union students carrying banner; Marry Curry, ?, Karen Humphrey, ?, Dale Doig